Golimumab for the treatment of axial spondyloarthritis. (2nd January 2017) - Palazzi, Carlo; D'angelo, Salvatore; Gilio, Michele; Leccese, Pietro; Padula, Angela; Olivieri, Ignazio
ABSTRACT: Introduction : Anti-TNF drugs have represented an epochal revolution in the treatment of rheumatoid arthritis and spondyloarthritis. In the field of axial spondyloarthritis, golimumab, a fully human monoclonal anti-TNFα administered subcutaneously every 4 weeks, has shown significant efficacy and good safety in patients with ankylosing spondylitis. More recently, it was also indicated as an effective treatment for patients suffering from non-radiographic axial spondyloarthitits. Areas covered : A systematic literature search was completed, using the largest electronic databases (Medline, Embase and Cochrane), with the aim to review all data concerning the administration of golimumab in patients suffering from axial spondyloartritis. Expert opinion : In the 16-week GO-AHEAD study, golimumab was effective in patients with non-radiographic spondyloarthritis with high levels of CRP and/or positive MRI findings, but not in subjects with both negative CRP and MRI. This finding allows for the addressing the of anti-TNF treatment more specifically. Preliminary data concerning an open-label extension of the GO-AHEAD study outlined the high retention-rate of the drug at 52 weeks. The production of antibodies against golimumab is rare and it seems to exert scarce influence on the drug performances. In conclusion, golimumab appears as a very useful and well tolerated anti-TNF agent.